2010
DOI: 10.1007/s10661-010-1347-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ground-level fireworks (13 km long) display on the air quality during the traditional Yanshui Lantern Festival in Taiwan

Abstract: In this study, the concentrations of CO, non-methane hydrocarbons, NO(X), SO(2), benzene, toluene, ethylbenzene, xylene (BTEX), PM₁₀, and PM₂.₅ were continuously monitored before and after the fireworks display during the traditional Lantern Festival from March 2-7, 2007 in Yanshui Town, Taiwan. Major roads in Yanshui Town were surrounded by fireworks 13 km in length, with the display lasting for 45 min. More than 200 small firecracker towers popped up randomly in town, resulting in exceedingly inhomogeneous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 14 publications
1
32
1
Order By: Relevance
“…The PM 2.5 concentrations recorded in the current study during a Yanshui beehive firework display did not match with those measured by Chang et al (2011) and Lin et al (2014). The mismatch could result from the difference in the monitoring locations, data resolutions, and meteorological conditions.…”
Section: Meteorological Conditions During the Beehive Firework Displacontrasting
confidence: 78%
See 4 more Smart Citations
“…The PM 2.5 concentrations recorded in the current study during a Yanshui beehive firework display did not match with those measured by Chang et al (2011) and Lin et al (2014). The mismatch could result from the difference in the monitoring locations, data resolutions, and meteorological conditions.…”
Section: Meteorological Conditions During the Beehive Firework Displacontrasting
confidence: 78%
“…In the current study, the 5-min maximum PM 2.5 concentration during the episode period increased to 593.9 µg m -3 , which was 22 times the value during the nonepisode period. Chang et al (2011) observed that the PM 2.5 concentration during a Yanshui beehive firework display reached 250 µg m -3…”
Section: Meteorological Conditions During the Beehive Firework Displamentioning
confidence: 98%
See 3 more Smart Citations